Examining the Cultuling of Liminality Using Binary Oppositions in Light of Hymes’ SPEAKING Model - Reza Pishghadam; Shima Ebrahimi (̒Ilm-i Zabān, 2020)
Binary oppositions have long been helping humans to label what is going on around, and sometimes put them on the horns of a dilemma. Such a reflection can be traced in people’s cultures, and since language is an indispensable part of a culture, examining cultulings (culture + language) can help us understand the beliefs and values of a given society. The present study, therefore, utilizes Hymes’ (1967) SPEAKING model to qualitatively analyze “the Cultuling of Liminality.” To this end, 712 contexts and 317 utterances, in which binary oppositions had been used were chosen based on purposive sampling and by observing private/public, formal/informal dialogues from 115 female and 97 male speakers (15 to 74 years old), from different academic backgrounds, professions, and social status from Mashhad, Iran. The results indicated that Iranians use this cultuling for different purposes (e.g., showing uncertainty, avoiding direct remarks and misunderstandings, defending, shirking responsibilities, showing mental struggles, avoiding stress, observing formalities, and lack of knowledge) in different contexts. This cultuling can be used as an indicator of high ambiguity intolerance in Iranian culture, meaning that they do not like to be in limbo, and due to their collectivist nature, they use binary oppositions to express their suspense to directly/indirectly ask for help to make decisions and to be out of liminality.